Natural variation of FKF1 controls flowering and adaptation during soybean domestication and improvement. Issue 4 (12th March 2023) - Li, Haiyang; Du, Haiping; He, Milan; Wang, Jianhao; Wang, Fan; Yuan, Wenjie; Huang, Zerong; Cheng, Qun; Gou, Chuanjie; Chen, Zheng; Liu, Baohui; Kong, Fanjiang; et al.
Summary: Soybean ( Glycine max ) is a major source of protein and edible oil world‐wide and is cultivated in a wide range of latitudes. However, it is extremely sensitive to photoperiod, which influences flowering time, maturity, and yield, and severely limits soybean latitude adaptation. In this study, a genome‐wide association study (GWAS) identified a novel locus in accessions harboring the E1 allele, called Time of flowering 8 ( Tof8 ), which promotes flowering and enhances adaptation to high latitude in cultivated soybean. Gene functional analyses showed that Tof8 is an ortholog of Arabidopsis FKF1 . We identified two FKF1 homologs in the soybean genome. Both FKF1 homologs are genetically dependent on E1 by binding to E1 promoter to activate E1 transcription, thus repressing FLOWERING LOCUS T 2a ( FT2a ) and FT5a transcription, which modulate flowering and maturity through the E1 pathway. We also demonstrate that the natural allele FKF1b H3 facilitated adaptation of soybean to high‐latitude environments and was selected during domestication and improvement, leading to its rapid expansion in cultivated soybean. These findings provide novel insights into the roles of FKF1 in controlling flowering time and maturity in soybean and offer new means to fine‐tune adaptation to high latitudes and increase grain yield.